The future of hyperdiverse tropical ecosystems - Barlow, Jos; França, Filipe; Gardner, Toby A.; Hicks, Christina C.; Lennox, Gareth D.; Berenguer, Erika; Castello, Leandro; Economo, Evan P.; Ferreira, Joice; Guénard, Benoit; Gontijo Leal, Cecília; Isaac, Victoria; et al. (Nature (London), 2018)
The tropics contain the overwhelming majority of Earth’s biodiversity: their terrestrial, freshwater and marine ecosystems hold more than three-quarters of all species, including almost all shallow-water corals and over 90% of terrestrial birds. However, tropical ecosystems are also subject to pervasive and interacting stressors, such as deforestation, overfishing and climate change, and they are set within a socio-economic context that includes growing pressure from an increasingly globalized world, larger and more affluent tropical populations, and weak governance and response capacities. Concerted local, national and international actions are urgently required to prevent a collapse of tropical biodiversity. The immense biodiversity of tropical ecosystems is threatened by multiple interacting local and global stressors that can only be addressed by the concerted efforts of grassroots organizations, researchers, national governments and the international community.